2012
DOI: 10.1002/pssa.201228014
|View full text |Cite
|
Sign up to set email alerts
|

Thickness study of AZO films by RF sputtering in Ar + H2 atmosphere at room temperature

Abstract: Al‐doped ZnO (AZO) films were prepared on glass substrates by RF magnetron sputtering in an Ar + 5%H2 ambient at room temperature. The influence of film thickness (85–1101 nm) on the structural, electrical, and optical properties of the films was investigated. With increasing film thickness, it is found that the crystallinity of the films is improved and the surface roughness of the films increases. The decrease of resistivity is accompanied by an increase of carrier concentration and mobility. At the film thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…[11][12][13][14][15][16][17] However, it must be remembered that ρ and n (but not μ) require knowledge of the electrical thickness d el , which may not be the same as d. That is, the Hall effect does not directly measure a volume concentration n ðcm −3 Þ, but a sheet concentration n s ðcm −2 Þ. If n is uniform, then these two quantities are simply related by n ¼ n s ∕d el , where d el ¼ d − δd is the electrical thickness, the region that contains free electrons.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] However, it must be remembered that ρ and n (but not μ) require knowledge of the electrical thickness d el , which may not be the same as d. That is, the Hall effect does not directly measure a volume concentration n ðcm −3 Þ, but a sheet concentration n s ðcm −2 Þ. If n is uniform, then these two quantities are simply related by n ¼ n s ∕d el , where d el ¼ d − δd is the electrical thickness, the region that contains free electrons.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…[5][6][7][8][9][10] The attractiveness of ZnO in these applications is partially due to the demonstrations of high-quality growth on many different substrates using many different growth techniques. However, a troubling problem is that films on lattice-mismatched substrates nearly always exhibit a thickness dependence of the electrical parameters, resistivity ρ, mobility μ, and carrier concentration n. [11][12][13][14][15][16][17] The origin of this problem seems to be connected with poor crystallinity near the substrate/layer interface. Recently, however, Itagaki et al 16,18,19 have demonstrated significant improvement in the crystallinity of radio frequency (RF)-sputtered ZnO by inserting a thin ZnON buffer layer between the substrate and ZnO layer.…”
Section: Introductionmentioning
confidence: 99%
“…The attractiveness of ZnO in these applications is partially due to the demonstrations of high-quality growth on many different substrates using many different growth techniques. However, a troubling problem is that films on lattice-mismatched substrates nearly always exhibit a thickness dependence of the electrical parameters, resistivity ρ, mobility µ, and carrier concentration n [11][12][13][14][15][16][17]. The origin of this problem seems to be connected with poor crystallinity near the substrate/layer interface.…”
Section: Introductionmentioning
confidence: 95%
“…The mostly used ZnO:Al thin film has been prepared with various methods: radio frequency (RF) sputtering [7], pulsed laser deposition [8], atomic layer deposition and chemical vapor deposition [9]. Many authors have studied the RF sputtering of ZnO:Al target [10][11][12][13]. Unfortunately, only few studies reported on doping by simultaneous magnetron co-sputtering techniques [14], the most important advantage of this method is the control of the charges carrier concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The films present good thermal stability, they are abundant, non toxic and not expensive [6]. The mostly used ZnO:Al thin film has been prepared with various methods: radio frequency (RF) sputtering [7], pulsed laser deposition [8], atomic layer deposition and chemical vapor deposition [9]. Many authors have studied the RF sputtering of ZnO:Al target [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%